Estimasi Populasi Bajing Kelapa (Callosciurus notatus Boddaert, 1785) Famili Sciuridae di Nagari Koto Dalam, Kecamatan Padang Sago, Sumatera Barat - Andalisa, Lusi; Rizaldi, Rizaldi; Nurdin, Jabang (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018), 2018)
Estimation of the plantain squirrel ( Callosciurus notatus Boddaert, 1785) population was conducted from Februari to May 2016. This study aimed to estimate population density in the traditional coconut plantation, Nagari Koto Dalam, Padang Pariaman. The population density was estimated using line transect survey method. Population density of the squirrels in Nagari Koto Dalam was 5.5 ind/ha. This study shows that population density of the squirrel comparable to previous studies in West Sumatra.